Indeks Literasi Digital Siswa MTs Kecamatan Pabelan, Semarang dan Kecamatan Kalasan, Sleman (Universitas Muhammadiyah Purworejo, 2023)
Communication and information technology has built modern civilization, where communication is no longer in a vacuum, nor in the context of homogeneity. Through research on the digital literacy index of teenagers at Islamic Junior High School (MTs) in Pabelan District, Semarang Regency and Kalasan District, Sleman Regency, the objectives to be achieved are: (1) Mapping the level of digital literacy of MTs students, (2) Mapping the ability of MTs students in using digital media (3) Assisting local governments in making decisions regarding literacy education format issues digital that suits the conditions in the school. In this research the author uses quantitative research methods with an explanatory research format. This survey method is carried out by distributing questionnaires. The results showed that the literacy level of MTs students in Pabelan and Kalasan District was 4.1, included in the medium category. A total of 2 of the 8 indicators used produced a high category index, namely an index of Cultural dan Social Understanding and E-Safety, while the other 6 were included in the medium category. Based on these results, it can be categorized that MTs students in Pabelan and Kalasan Districts already have knowledge about the digital world in the moderate category.